Challenges and aspirations: lived experiences of teacher-education student-mothers of a state university - Fabillar, Jonas P.; Once, Ferdinand P.; Gabon, Veronica A. (Intelektual Pustaka Media Utama, 2025)
The COVID-19 pandemic has caused significant disruptions in education globally leading to the implementation of different learning modalities. And it highly affects the most vulnerable groups such as women and children. This study explored the lived experiences of teacher-education student-mothers of a state university in the Philippines towards the end of the pandemic using a phenomenological approach. Twenty-one student-mothers voluntarily participated in the study who were i) bona fide students of the campus, ii) biological mothers, iii) married or living together with a partner, and iv) living with their child. From the data analyses, four major themes emerged: i) unexpected pregnancy, ii) heightened stress during the pandemic, iii) maintaining a positive outlook in life, and iv) managing dual roles. These results implied that the teacher-education student-mothers were highly stressed during the pandemic but they had extrinsic motivators to finish studies such as their children and family. The lived experiences of teacher-education student-mothers can serve as an inspiration to other students to pursue their studies even amid adversities. It is recommended that there be an enhancement of student services tailored to support the mental health of marginalized students.